Selective modes affect gene feature and function differentiation of tetraploid Brassica species in their evolution and domestication - Wei, Dayong; Li, Nan; Zhang, Nan; Liu, Feng; Wu, Jie; Zhao, Sa; Shen, Jinjuan; Wang, Zhimin; Peng, Lisha; Fan, Yonghong; Mei, Jiaqin; Tang, Qinglin (Frontiers in Plant Science, 2023)
The genus Brassica contains a diverse group of important vegetables and oilseed crops. Genome sequencing has been completed for the six species (B. rapa, B. oleracea, B. nigra, B. carinata, B. napus, and B. juncea) in U’s triangle model. The purpose of the study is to investigate whether positively and negatively selected genes (PSGs and NSGs) affect gene feature and function differentiation of Brassica tetraploids in their evolution and domestication. A total of 9,701 PSGs were found in the A, B and C subgenomes of the three tetraploids, of which, a higher number of PSGs were identified in the C subgenome as comparing to the A and B subgenomes. The PSGs of the three tetraploids had more tandem duplicated genes, higher single copy, lower multi-copy, shorter exon length and fewer exon number than the NSGs, suggesting that the selective modes affected the gene feature of Brassica tetraploids. The PSGs of all the three tetraploids enriched in a few common KEGG pathways relating to environmental adaption (such as Phenylpropanoid biosynthesis, Riboflavin metabolism, Isoflavonoid biosynthesis, Plant-pathogen interaction and Tropane, piperidine and pyridine alkaloid biosynthesis) and reproduction (Homologous recombination) . Whereas, the NSGs of the three tetraploids significantly enriched in dozens of biologic processes and pathways without clear relationships with evolution. Moreover, the PSGs of B. carinata were found specifically enriched in lipid biosynthesis and metabolism which possibly contributed to the domestication of B. carinata as an oil crop. Our data suggest that selective modes affected the gene feature of Brassica tetraploids, and PSGs contributed in not only the evolution but also the domestication of Brassica tetraploids.